Temperature and pH-sensitive chitosan-collagen hydrogels for antimicrobial and wound healing applications - Ud Din, Aiman Salah; Ashraf, Azqa; Hussain, Mudassar; Ahmad, Adnan; Khan, Imad; AL-Ansi, Waleed; Zou, Xiaoqiang (International Journal of Environment, Agriculture and Biotechnology, 2023)
Hydrogels have proven to be of great value because of their useful properties and functions. Temperature and pH-sensitive chitosan-collagen-based hydrogels have drawn research interest in the area of wound care. Their unique mechanism allows them to release antimicrobial agents in response to changes in the environment and aids in efficient healing of wounds. The current review aims to describe various composite hydrogels of chitosan and collagen, their temperature and pH sensitivity, the antimicrobial effect of chitosan-collagen hydrogels and their applications in wound healing. Sources and properties of chitosan and collagen have also been stated in order to highlight their importance in these hydrogels. The main focus revolves around the potential of chitosan-collagen hydrogels as antimicrobial biomaterials for healing wounds in an efficient manner.